2020
DOI: 10.1371/journal.pgen.1008856
|View full text |Cite
|
Sign up to set email alerts
|

Repression of tick microRNA-133 induces organic anion transporting polypeptide expression critical for Anaplasma phagocytophilum survival in the vector and transmission to the vertebrate host

Abstract: The microRNAs (miRNAs) are important regulators of gene expression. In this study, we provide evidence for the first time to show that rickettsial pathogen Anaplasma phagocytophilum infection results in the down-regulation of tick microRNA-133 (miR-133), to induce Ixodes scapularis organic anion transporting polypeptide (isoatp4056) gene expression critical for this bacterial survival in the vector and for its transmission to the vertebrate host. Transfection studies with recombinant constructs containing tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 66 publications
(141 reference statements)
1
52
0
Order By: Relevance
“…Larvae were allowed to feed on naïve mice and allowed to molt into nymphs, generating uninfected nymphs. Tick rearing was conducted in an incubator at 23 ± 2 °C and 90–95% relative humidity under a 14/10-h light/dark photoperiod regimen, as described in our previous studies [ 17 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Larvae were allowed to feed on naïve mice and allowed to molt into nymphs, generating uninfected nymphs. Tick rearing was conducted in an incubator at 23 ± 2 °C and 90–95% relative humidity under a 14/10-h light/dark photoperiod regimen, as described in our previous studies [ 17 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next-generation sequencing approach has identified a potential role of Ixodes scapularis tick miRNAs in viral replication including POWV (85), and LGTV (86). Our group has also recently shown that repression of tick miRNA facilitates rickettsial pathogen survival and transmission to the vertebrate host (87). Currently, microRNA-targeting has been developed as an active strategy for pathogenicity and for the selective control of tissue-tropism of RNA viruses (88).…”
Section: Putative Roles For Noncoding Rnas In Modulation Of Tetraspaninsmentioning
confidence: 99%
“…The Eppendorf FemtoJet microinjection system was used in this study. Microinjections into ticks were performed as previously described 36 . The DC preparation (as described in an earlier methods section) from A. phagocytophilum-infected HL-60 was tenfold serially diluted twice and the diluted solution was used for microinjections into ticks.…”
Section: Scientific Reportsmentioning
confidence: 99%